1996
DOI: 10.3382/ps.0750042
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Escherichia coli 0157:H7 Strain 932 to Selected Anticoccidial Drugs in Broiler Chicks

Abstract: The ability of selected anticoccidial drugs to inhibit the colonization of day-old male broiler chicks (Cornish Rocks) by Escherichia coli O157:H7, strain 932 was examined. Chicks were challenged with 1.8 x 10(9) E. coli O157:H7 on Day 1, and fed diets supplemented with three selected anticoccidial drugs; monensin, nicarbazin, or robenidine. The cecal and colon fecal contents of the chicks were removed on Day 7, 14, and 21 postinoculation and examined for the concentration of E. coli O157: H7 per gram of conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…It is well known from the literature that dehydroacetic acid (3-acetyl-6-methyl-pyran-2,4-dione) have a strong ability to form metal complexes. Besides its chelating ability, it also shows promising antifungal, antibacterial and antiprototozoal activities [9,10]. The present work deals with the studies of metal complexes of dehydroacetic acid and heterocyclic aldehydes so as to confirm whether there is enhancement in the biological activity due to complexation with transition metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known from the literature that dehydroacetic acid (3-acetyl-6-methyl-pyran-2,4-dione) have a strong ability to form metal complexes. Besides its chelating ability, it also shows promising antifungal, antibacterial and antiprototozoal activities [9,10]. The present work deals with the studies of metal complexes of dehydroacetic acid and heterocyclic aldehydes so as to confirm whether there is enhancement in the biological activity due to complexation with transition metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…The observations also indicated that monensin did not influence the shedding of Salmonella in naturally infected chickens. In chickens challenged with E. coli O 157, monensin reduced the number of this strain in caecum and colon, to the extent that by day 21 no E. coli O 157:H7 were detected (Stanley, et al, 1996). However, it should be noted that the dose used (227 mg kg -1 feed) was substantially above the maximum dose recommended.…”
Section: /61mentioning
confidence: 92%
“…Dehydroacetic acid (3‐acetyl‐4‐hydroxy‐6‐methyl‐2 H ‐pyran‐2‐one) was reported to be an excellent chelating agent and possesses promising fungicidal, bactericidal, herbicidal, and insecticidal activities , it is also a versatile starting material for the synthesis of a wide variety of heterocyclic ring systems.…”
Section: Introductionmentioning
confidence: 99%